(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Energy Management systems (EnMS) is an effective measure to manage energy utilization, drive for continuous improvement in energy performance and sustain business competitiveness. The public expectations i.e., greenhouse gas emission limits and zero liquid discharge will put additional burdens to oil companies. Many companies have initiated to deploy energy program in response to these concerns. However, impact of implementing the program has just been seen. Concerned companies are far away from achieving an appropriate expectations. Most of oil companies consider EnMS as an ambition, rather than an important criterion to be applied in all levels of the businesses. To overcome the abovementioned issues, this paper presents proven approaches to manage the energy efficiency. As for the primary objective, it presents a customized EnMS in enhancing utilization of energy resources. The customized EnMS has been established in accordance to expectations of international industrial best practices. It can be divided into: (1) establish energy visions, (2) select energy performance indicators, (3) identify energy improvement approaches and (4) monitor and manage energy performance tracking. In addition, case studies and best practices are also included in the customized EnMS to address the flexibilities. The second objective is to describe systematic tactics to expedite the effective implementation of EnMS. Tactics include: engage higher management commitment, subscribe to reputable standards, impels for energy savings and embed EnMS into existing management programs. Energy improvement tips are also included into comprehensive framework. Lastly, the third objective is to illustrate the customized EnMS at an undisclosed oil company.